2017
DOI: 10.1007/s12192-016-0743-z
|View full text |Cite|
|
Sign up to set email alerts
|

Encapsulated Hsp70 decreases endotoxin-induced production of ROS and TNFα in human phagocytes

Abstract: Human heat shock protein Hsp70 was experimentally inserted into polyelectrolyte microcapsules. Encapsulated recombinant Hsp70 was studied in terms of its effects on neutrophil apoptosis, the production of reactive oxygen species, and the secretion of tumor necrosis factor alpha by promonocytic THP-1 cells. It was found that encapsulated Hsp70 effectively inhibits neutrophil apoptosis, unlike free exogenous protein used in solution. In THP-1 cells, encapsulated and free Hsp70 reduced LPS-induced tumor necrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 54 publications
0
3
0
1
Order By: Relevance
“…The role of Hsp70 in maintaining redox homeostasis and inhibiting oxidative stress in organisms and cells under stressful conditions has been reported in several higher animals and model organisms. Yurinskaya et al ( 2017 ) found that endotoxin can induce an increase in ROS levels in cultured human macrophages, but the addition of exogenous recombinant human Hsp70 results in a significant reduction. Jiang et al ( 2020 ) showed that cytoplasmic exosome-induced Hsp70 significantly reduces ROS levels in mice with cerebral ischemia/reperfusion, thereby attenuating cerebral ischemia/reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Hsp70 in maintaining redox homeostasis and inhibiting oxidative stress in organisms and cells under stressful conditions has been reported in several higher animals and model organisms. Yurinskaya et al ( 2017 ) found that endotoxin can induce an increase in ROS levels in cultured human macrophages, but the addition of exogenous recombinant human Hsp70 results in a significant reduction. Jiang et al ( 2020 ) showed that cytoplasmic exosome-induced Hsp70 significantly reduces ROS levels in mice with cerebral ischemia/reperfusion, thereby attenuating cerebral ischemia/reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Hsp70 exerts antioxidative stress effects by increasing antioxidant enzyme activity, e.g., SOD, glutathione peroxidase (GPx), and CAT ( Broome et al, 2006 ; Gu et al, 2012 ; Xu et al, 2018 ), binding and antagonizing polymerized glyceraldehyde 3-phosphate dehydrogenase (GAPDH) ( Lazarev et al, 2016 ), promoting SOD2 transport to mitochondria ( Afolayan et al, 2014 ), maintaining glutathione (GSH) levels in cells ( Broome et al, 2006 ), and regulating nicotinamide adenine dinucleotide phosphate oxidase (NOX) enzymatic activity ( Chen et al, 2012 ; Troyanova et al, 2015 ). The antioxidative stress effects of Hsp70 have been explored in humans ( Homo sapiens ) ( Afolayan et al, 2014 ; Jiang et al, 2020 ; Yurinskaya et al, 2017 ), rats ( Rattus norvegicus ) ( Lazarev et al, 2016 ; Liu et al, 2015 ), mice ( Mus musculus ) ( Broome et al, 2006 ; Hernández-Santana et al, 2014 ), chickens ( Gallus gallus ) ( Gu et al, 2012 ), and fruit flies ( Drosophila melanogaster ) ( Gupta et al, 2007 ). To date, however, regulation of redox homeostasis by Hsp70 in fish under stressful conditions has only been reported in rainbow trout ( Oncorhynchus mykiss ) ( Zeng et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also indicated that Hsp70 may decrease endotoxin-induced production of ROS and TNF-α in human phagocytes. 11…”
Section: Discussionmentioning
confidence: 99%
“…В регуляцию ультрафиолет-индуцированного апоптоза нейтрофилов вовлечены p38 MAPK (mitogen-activated protein kinase) и ERK (extracellular signal regulated kinase) [2,45]. Наряду с MAPK, важными регуляторами стресс-индуцированного апоптоза нейтрофилов являются белки теплового шока (Hsp (heat shock proteins)) [46].…”
Section: основные типы апоптоза нейтрофиловunclassified